The craft of intelligence - Dulles, Allen W. (Harper & Row, 1963)
"The former chief of the Central Intelligence Agency tells what he has learned from nearly a half-century of experience in diplomacy, international law, espionage, and the clandestine side of foreign affairs"--Jacket subtitle.